Linking white and grey matter in schizophrenia: oligodendrocyte and neuron pathology in the prefrontal cortex - Hoistad, Malin; Segal, Devorah; Takahashi, Nagahide; Sakurai, Takeshi; Buxbaum, Joseph D.; Hof, Patrick R. (Frontiers in Neuroanatomy, 2009)
Neuronal circuitry relies to a large extent on the presence of functional myelin produced in the brain by oligodendrocytes. Schizophrenia has been proposed to arise partly from altered brain connectivity. Brain imaging and neuropathologic studies have revealed changes in white matter and reduction in myelin content in patients with schizophrenia. In particular, alterations in the directionality and alignment of axons have been documented in schizophrenia. Moreover, the expression levels of several myelin-related genes are decreased in postmortem brains obtained from patients with schizophrenia. These findings have led to the formulation of the oligodendrocyte/myelin dysfunction hypothesis of schizophrenia. In this review, we present a brief overview of the neuropathologic findings obtained on white matter and oligodendrocyte status observed in schizophrenia patients, and relate these changes to the processes of brain maturation and myelination. We also review recent data on oligodendrocyte/myelin genes, and present some recent mouse models of myelin deficiencies. The use of transgenic and mutant animal models offers a unique opportunity to analyze oligodendrocyte and neuronal changes that may have a clinical impact. Lastly, we present some recent morphological findings supporting possible causal involvement of white and grey matter abnormalities, in the aim of determining the morphologic characteristics of the circuits whose alteration leads to the cortical dysfunction that possibly underlies the pathogenesis of schizophrenia.